Determinant of knowledge management in higher education of Nigeria (a case study of University of Lagos) - Omolara, Salisu Idayat (Kuliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Knowledge is the supreme strategic resources that can be owned by an organisation, and they jealously protect it. Knowledge Management is understood to be the certification, optimization, and that guide the present management of unphysical assets, that can be in form of embedded acquaintance that is possessed by an individual or acquaintances that is written and pass on to people to take advantage of; which could be in form of researches, text books and even manuals. This curve out the objective of the study, to identify issues affecting Knowledge management in university of Lagos. To explain effective knowledge management, it has to do with the formation and the appropriateness in disseminating knowledge. The study also like to view the advantage of adopting knowledge management system, as development of information and technology have rapidly advent most developing nations sectors, although educational sector have a setback when it comes to IT in Nigeria . Nonetheless the best way for educator conveyance of tactic ideas to the plainest intellectual to be internalise by student or learners is also reviewed. Sequel to this, information is attributed as a key in this study because it is used for adaptation process. Because student derive tactic knowledge from the information that follows within their reach. A quantitative method is used by the means of questionnaire. That was directed to 100 lecturers of 5 department in university of Lagos. The data was collected and analysed using SPSS; running in frequencies and percentages. The study results shows that there is significances connection concerning the independent variables (creation, sharing/ dissemination and storage) and the dependent (knowledge management). All test carried out arrive positive and relevance of the study was exposed. It is form this research that most of the lecturers actually understood the need for the Knowledge Management, even though some claim they practise it. While to some it a new idea that will like to welcome.